?POLLUTION DUE TO EFFLUENTS FROM TANNERIES/LEATHER INDUSTRIES IN N.W.F.P. (Biological Sciences - PJSIR, 1995)
Physico-chemical parameters of effluents from Tanneries (vegetable and chrome tanneries) were studied. The tan- neries effluents usually discharged into the rivers streams without any pre-treatment were found to have high load of solids, COD, sulfides, phenols and chromium beside being highly coloured. The continued uncontrolled discharge of effluents with heavy pollution load would cause the deterioration of the ground water as well as adversely affcctS the surrounding environments of the tanneries/leather industries.